THE TWO POLES OF LITERARY PRODUCTION: HETERONOMY, AUTONOMY AND THE LITERARY FIELD IN THE THEORY OF PIERRE BOURDIEU (Journal of Contemporary Philology, 2021)
The literary world has always been marked by the debate on the legitimacy of literary works. Whothe literary works are written for, who they should be written for, and how one should write them. Additionally, a plethora of other similar questions have been raised, time and time again, with statistical regularity, especially after the establishment of literature as an autonomous field at the end of the 18th and the beginning of the 19th century. In this paper, the importance of this type of conflict in the field of literature will be analyzed by examining two such instances in literature - Paulo Coelho and H.G. Wells’ criticism of Ulysses and Finnegan’s Wake by James Joyce and the contrasting views of the poet and criticT.S. Eliot. Pierre Bourdieu’s theories will serve as our main methodological tool in this analysis, particularly his concept of field, specifically addressing the literary field. We will further analyze the indicated examples by opposing the two poles of functioning of the literary field: restricted production and large-scaleproduction - a binary opposition that logically stems from the dual hierarchization of the field. According to Bourdieu, conflicts of this kind stem from the very structure of the literary field itself, and help legitimize it as an autonomous module of cultural production as well as drive its production and reproduction within societal reality.
Keywords: literary debate; Pierre Bourdieu; field; commercial literature; cultural production; literary field